Inclusion of Fingerprints in Notarial Deed Minutes as a Guarantee of Legal Protection for the Parties - Ariany, Erry; Santiago, Faisal (Jurnal Greenation Sosial dan Politik, 2025)
The position of Notary is a profession that requires special skills and high responsibility in serving the legal needs of the community. However, in practice, there are often deviations by the parties appearing before the Notary, such as the party that should be listed in the deed is not the person who is present in person or denying the existence of a transaction made before the Notary. To protect the validity of the deed and the position of the Notary, one of the provisions regulated in Article 16 paragraph (1) letter c of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary is the obligation to include the fingerprints of the parties on the minutes or attachments to the deed. This study aims to examine and analyze the importance of these provisions in guaranteeing the authenticity of the identity of the parties, preventing legal defects in the deed, and ensuring its legal accountability. By using a normative legal approach based on statutory regulations, this study concludes that the regulation regarding fingerprints in the minutes of notarial deeds still gives rise to various interpretations, so strict supervision is needed from the Notary Supervisory Board to impose sanctions if there is negligence by the Notary in its implementation.